2011
DOI: 10.1002/jmri.22417
|View full text |Cite
|
Sign up to set email alerts
|

Single region of interest versus multislice T2* MRI approach for the quantification of hepatic iron overload

Abstract: Purpose: To evaluate the effectiveness of the single ROI approach for the detection of hepatic iron burden in thalassemia major (TM) patients in respect to a whole liver measurement. Materials and Methods:Five transverse hepatic slices were acquired by a T2* gradient-echo sequence in 101 TM patients and 20 healthy subjects. The T2* value was calculated in a single region of interest (ROI) defined in the medium-hepatic slice. Moreover, the T2* value was extracted on each of the eight ROIs defined in the functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
66
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 25 publications
3
66
0
Order By: Relevance
“…Meloni et al demonstrated that liver T2* variations were limited and when present they were secondary to artifact or measurement variability [14]. In an attempt to negate the presence of any sampling bias, we calculated average T2* values obtained from nine ROI, divided into seven wedges.…”
Section: Discussionmentioning
confidence: 99%
“…Meloni et al demonstrated that liver T2* variations were limited and when present they were secondary to artifact or measurement variability [14]. In an attempt to negate the presence of any sampling bias, we calculated average T2* values obtained from nine ROI, divided into seven wedges.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of our method could be that it is an ROI-based method. Meloni et al evaluated the effectiveness of the single ROI approach and found that it slightly underestimates liver iron quantification due to susceptibility artifacts when the ROI was placed over segments VII and VIII [28]. They concluded that the single ROI approach can be safely used in the clinical area when taking care to avoid susceptibility artifact effect.…”
mentioning
confidence: 99%
“…Alternatives are global analysis including the full extent of the liver within the slice, but excluding obvious major hilar vessels [5, 15], and ROI defined in an area of homogeneous liver tissue, avoiding blood vessels and other sources of artifacts [1618]. …”
Section: Methodsmentioning
confidence: 99%
“…Alternatives are averaged-signal or region-based analysis, where pixels within the ROI are averaged together and fit is performed for this averaged decay curve [17, 18], and pixelwise analysis, where fitting is performed for each pixel within the ROI and the median of the distribution of R2* values is calculated [5, 15]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation